Why Are Traditional Games Good for The Physical Being? - Arfanda, Poppy Elisano; Aprilo, Ians; Mappaompo, M. Adam; Arimbi, Arimbi; Muhammad, Heryanto Nur (Department of Physical Education, Sport, Health and Recreation, 2024)
This paper aims to increase the physical activity of children and adolescents with traditional games based on a literature review by analyzing relevant articles. Literature review obtained from. Google Scholar, Scopus, Science Direct, Web of Science, and Crossref with the keywords traditional games to physical activity and physical components. The literature used starts from 2014-2023. The literature search was carried out until December 2023. 49 articles were selected from the 200 articles found. From this literature, it is found that traditional games can have a physical influence, namely the development of gross and fine motor skills, the development of basic locomotor, non-locomotor, and manipulative movements, balance, speed, agility, accuracy, and endurance. Traditional games also influence character, namely training patience and perseverance, fostering imagination and creativity, problem-solving abilities, and fighting power. Meanwhile, moral influences are cooperation, honesty, responsibility, hard work, discipline, self-confidence, and tolerance. The social influence caused by traditional games is to establish social relationships and comfort.